2010
DOI: 10.1093/hmg/ddq008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Cullin 4B result in a human syndrome associated with increased camptothecin-induced topoisomerase I-dependent DNA breaks

Abstract: CUL4A and B encode subunits of E3-ubiquitin ligases implicated in diverse processes including nucleotide excision repair, regulating gene expression and controlling DNA replication fork licensing. But, the functional distinction between CUL4A and CUL4B, if any, is unclear. Recently, mutations in CUL4B were identified in humans associated with mental retardation, relative macrocephaly, tremor and a peripheral neuropathy. Cells from these patients offer a unique system to help define at the molecular level the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…Despite the largely overlapping functions of CUL4A and CUL4B, recent studies also revealed distinct roles for the two CUL4 family members in DNA-damage response, male meiosis, and response to environmental toxins [12][13][14][15]. While CUL4B compensates for the loss of CUL4A [12], CUL4A expression, which is unaffected by CUL4B mutations [16], is apparently unable to rescue the neuronal and developmental deficiencies found in CUL4B patients with XLMR. Notably, the loss of CUL4B function is not lethal in humans [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the largely overlapping functions of CUL4A and CUL4B, recent studies also revealed distinct roles for the two CUL4 family members in DNA-damage response, male meiosis, and response to environmental toxins [12][13][14][15]. While CUL4B compensates for the loss of CUL4A [12], CUL4A expression, which is unaffected by CUL4B mutations [16], is apparently unable to rescue the neuronal and developmental deficiencies found in CUL4B patients with XLMR. Notably, the loss of CUL4B function is not lethal in humans [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The complexes formed by cullins, Cul4A and Cul4B, with DDB1 have been implicated in several different aspects of genome maintenance, including the repair of DNA damage caused by UV light (27)(28)(29), replication licensing (30 -32), DNA damageand stress-activated signaling (33,34), replication-associated nucleosome assembly (35), and DNA polymerase ␦ (Pol␦) subunit structure (36,37). Furthermore, mutations in CUL4B have been identified in humans with mental retardation, macrocephaly, and peripheral neuropathy with cell lines from these patients exhibiting defects in the repair of camptothecin-induced DNA single-strand breaks (38).…”
Section: Discussionmentioning
confidence: 99%
“…4B). Two Cul4 paralogs, Cul4A and Cul4B, exist in mammals; they share 82% sequence identity, both interact with DDB1, and they have been shown to play redundant roles in some contexts (55,56,70,71). Overexpression of Cul4A led to reduced FLAG-Pygo2 protein level in a dosage-dependent manner (Fig.…”
Section: The Intracellular Protein Level Of Pygo2/pygo2 Is Regulated mentioning
confidence: 98%